Anion vacancy-induced photochromism and lattice relaxation in yttrium oxyhydride - Halil Arslan; Alexei Kuzmin; Vinoth Kumar Kasi; Ilze Aulika; Dmitrii Moldarev; Daniel Primetzhofer; Maximilian Wolff; Inga Pudza; Ørnulf Nordseth; Smagul Karazhanov (Communications Materials)
Abstract Understanding the mechanism behind the photochromic properties and light-induced structural and chemical changes in yttrium oxyhydride remains a challenge. This lack of knowledge limits our ability to address degradation, enhance photochromic performance, control color, improve durability, and fully realize the material’s applications. Here, first-principles calculations indicate that anion vacancies may be responsible for the photochromic effect and other key properties of yttrium oxyhydride. These vacancies form deep localized energy levels in the band gap. Sunlight absorption transfers electrons from the valence band to these defect levels, altering the charge state of the vacancies and triggering both the photochromic effect and lattice relaxation. This relaxation involves yttrium cations shifting outward for positively charged vacancies and inward for negatively charged ones, thereby affecting the local environment around the yttrium cations by altering the second coordination shell. Using extended X-ray absorption fine structure spectroscopy on transparent and photo-darkened yttrium oxyhydride films, we show that UV light induces lattice relaxation in the second coordination shell, in agreement with first-principles calculations.